Thomas Keneally's Career and the Literary Machine - Henningsgaard, Per (UNIV QUEENSLAND AUSTRALIAN LITERARY STUDIES, 2021)
There is no doubt that Thomas Keneally’s Career and the Literary Machine will, for many years to come, be an indispensable resource for scholars writing about the works of Thomas Keneally. Of course, Keneally continues to produce new works – in 2020, for example, he published a new novel, The Dickens Boy – so, over time, Paul Sharrad’s scholarly monograph will be seen as increasingly incomplete. Indeed, the most recent of Keneally’s works that receives meaningful coverage in the book is the 2014 publication of the third volume in Keneally’s unique history of Australia; the series is titled Australians, and this volume is subtitled ‘Flappers to Vietnam’. Nonetheless, it is difficult to imagine a future scholar writing about any of the works produced in the first fifty years of Keneally’s career (Keneally’s first book was The Place at Whitton, which was published in 1964) without referencing Thomas Keneally’s Career and the Literary Machine; the depth and quality of the research is just that good.